Contexts of social participation in health: challenges for the effectiveness of the right to health in plural societies - Arena Ventura, Carla Aparecida [UNESP]; Fiorati, Jete Jane [UNESP]; Queiroz Bonato, Patricia de Paula; Eugenio, Samira Janis (Univ Estado Rio Janeiro, 2023)
The concept of health is not restricted to the lack of diseases, and comprehends concrete situations of life, named social determinants of health. In a context of profound social inequalities, which impair the exercise of the right to health, this articles aims at discussing movements to stimulate and challenges regarding social participation experienced abroad and in Brazil. This is a qualitative descriptive research, developed in two stages: through a narrative review of the literature on participative practices in the world (analyzed considering the WHO working regions) and data colected through interviews with sixteen members of the Municipal Health Council of a city in the state of Sao Paulo. Data from the interviews were analyzed through content analysis and resulted in the thematic category Participation, social control and local community, and in the following subcategories: The importance of the Municipal Health Council, Lack of Participative Culture and Lack of access to information and social (dis)control. In sum, authors emphasize the transformative role of the human rights framework, when it emerges from the mobilization of society, in plural contexts that value the autonomy and protagonismo different citizens.
Keywords: Social Participation; Human Rights; Right to Health; Development; Municipal Health Council; Legal Pluralism